Contemporary Islamic Education and the Challenges of Artificial Intelligence: Between Adaptation and Civilizational Ethics - Maruf Maruf; Adi Fadli; Abdul Mujib (JUPE : Jurnal Pendidikan Mandala, 2026)
The rapid development of Artificial Intelligence (AI) has brought significant transformation to various aspects of life, including Islamic education. This article comprehensively examines the dynamics of AI integration in contemporary Islamic education by focusing on two main dimensions: pedagogical adaptation and civilizational ethics. Through a systematic literature review of recent academic publications (2022-2026), this study analyzes the opportunities, challenges, and relevant ethical frameworks within the context of maqāṣid al-sharī'ah. The findings show that AI offers transformative potential for learning personalization, knowledge accessibility, and teaching effectiveness, yet it also raises ethical challenges related to the erosion of religious authority, algorithmic bias, data privacy, and the dehumanization of learning processes. This article proposes an integrative framework based on Islamic values that positions AI as a wasilah (instrument) regulated within the corridor of maqāṣid al-sharī'ah to ensure that technology functions as a means of strengthening spiritual, moral, and humanistic values in Islamic education in the Society 5.0 era.